Mechanism unravelling for highly efficient and selective 99TcO4− sequestration utilising crown ether based solvent system from nuclear liquid waste: experimental and computational investigations. Issue 6 (25th January 2022) - Patra, Kankan; Sengupta, Arijit; Boda, Anil; Ali, Musharaf; Mittal, V. K.; Valsala, T. P.; Kaushik, C. P.
Abstract : Highly efficient and selective 99 TcO4 − sequestration utilising crown ether based solvent system from reprocessing low level liquid waste. Abstract : Selective and efficient separation of pertechnetate (TcO4 − ) from nuclear waste is desirable for the safe and secure management of radioactive waste. Here, we have projected dibenzo-18-crown-6 ether (DB18C6) in a highly polar nitrobenzene medium for enhancing the removal efficiency of 99 Tc from reprocessing plant low level waste (LLW). An effort was made to determine the stoichiometry of metal–ligand complex by slope ratio method, revealing that one ligand (DB18C6) binds with one TcO4 − moiety. Optimum ligand concentration for 99 Tc extraction was evaluated. Relevant interference of the anions was studied systematically. The effect of solution pH was analysed on the extraction efficiency of 99 Tc. A kinetic study was carried out for maximum extraction of metal ions. A quantitative stripping study was also achieved for metal ions with a suitable stripping solution. After evaluation of all essential parameters, selectivity and feasibility studies were finally carried out with actual low level reprocessing plant waste to demonstrate a laboratory scale process for effective separation of TcO4 − ions. Density functional theory (DFT) calculations were carried out to understand the nature of the complexation of TcO4 − ion with DB18C6 in different solvents systems and to elucidate the key aspect behind ionic selectivity and enhanced the 99 Tc extraction efficiency of DB18C6 in the studied diluent systems. The Δ E and Δ G values for different modeled complexation reactions were evaluated systematically. From the calculated free energy of complexation of TcO4 − with DB18C6, it was observed that the consideration of explicit solvent plays a vital role in predicting the experimental selectivity.